VD_FINDINFO Jug / 2015 / 115 vom 29. April 2015 - VD Tribunal cantonal (2015)
DIVORCE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE, PARTAGESENS GÉNÉRAL, PRESTATION DE LIBRE PASSAGE, PRÉVOYANCE PROFESSIONNELLE | 122 CC, 22 LFLP, 7 LPP, 8 LPP, 7 OLP, 8a al. 1 OLP, 8a OLP, 12 OPP2